The Effect of Job Mutation, Work Rotation on Performance with Job Satisfaction as an Intervening Variable in PLN UP3 Situbondo - Hotber Joy Hamonangan Sitanggang; Sugeng Mulyono; Jamal Abdul Nasir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the competitive global economy, optimizing human resource performance is crucial. Organizations frequently utilize job transfer and rotation policies to enhance adaptability and skills, yet their impact on employee performance remains inconsistent and warrants deeper investigation. This study aims to analyze the direct effects of job transfer and job rotation on employee performance, as well as their indirect effects through the intervening variable of job satisfaction at PT PLN UP3 Situbondo. A quantitative explanatory approach was employed, using a total sampling technique of 79 permanent employees. Data was collected via questionnaire and analyzed using Structural Equation Modeling (SEM) with the SmartPLS application. The results indicate that both job transfer and job rotation have a significant positive direct effect on employee performance. Furthermore, both variables also positively influence job satisfaction, which in turn significantly enhances performance. Importantly, job satisfaction is proven to act as a partial mediating variable in the relationship between both HR practices and employee performance. These findings emphasize the critical role of strategic implementation of transfer and rotation, supported by measures to increase job satisfaction, for improving overall employee productivity